The impact of Electronic Human Resource Management (E-HRM) on improving institutional performance at the Ministry of media in Riyadh - Almutairi, Shulaywih Hudayris (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to analyze the impact of electronic human resource management (e-HRM) on improving institutional performance at the Ministry of media in Riyadh. The researcher adopted a descriptive analytical methodology through a case study approach, collecting data via a questionnaire distributed to a small sample of 60 participants. The statistical analysis was conducted using SPSS software to test the study’s hypotheses. The findings revealed a significant positive impact of e-HRM on institutional performance, underscoring the importance of leveraging digital practices to enhance organizational efficiency.